Atypical Hemolytic Uremic Syndrome-Associated FHR1 Isoform FHR1*B Enhances Complement Activation and Inflammation - Xu, Boyang; Kang, Yuqi; Du, Yujing; Guo, Weiyi; Zhu, Li; Zhang, Hong (Frontiers in Immunology, 2022)
Atypical hemolytic uremic syndrome (aHUS) is a rare but severe type of thrombotic microangiopathy that is triggered by the abnormal activation of the alternative complement pathway. Previous studies have reported that three completely linked coding variants of CFHR1 form two haplotypes, namely, CFHR1*A (c.469C, c.475C, c.523G) and CFHR1*B (c.469T, c.475G, c.523C). CFHR1*B is associated with susceptibility to aHUS. To explore the genetic mechanism by which CFHR1 isoforms contribute to aHUS, we compared the structures of FHR1*A and FHR1*B by homology modeling and found differences in the angles between SCR3 and SCR4-SCR5, as FHR1*B had a larger angle than FHR1*A. Then, we expressed FHR1*A and FHR1*B recombinant proteins and compared their functions in complement system regulation and inflammation. We found that FHR1*B presented a significantly higher capacity for binding C3b and necrotic cells than FHR1*A. In a cofactor assay, the FHR-1*B showed stronger influence on FH mediated cofactor function than the FHR-1*A, resulted in fewer C3b cleavage products. In the C3 convertase assays, FHR1*B showed more powerful effect compared with FHR1*A regarding to de-regulate FH function of inhibition the assembling of C3bBb. Additionally, we also found that FHR1*B triggered monocytes to secrete higher levels of IL-1β and IL-6 than FHR1*A. In the present study, we showed that variants of CFHR1 might differently affect complement activation and sterile inflammation. Our findings provide a possible mechanism underlying the predisposition to aHUS caused by CFHR1 isoform CFHR1*B.